2011
DOI: 10.1007/s11999-011-1987-7
|View full text |Cite
|
Sign up to set email alerts
|

High Dislocation Cumulative Risk in THA versus Hemiarthroplasty for Fractures

Abstract: Background Although not all elderly patients with femoral neck fractures are candidates for THA, active, mentally competent, independent patients achieve the most durable functional scores with THA compared with hemiarthroplasty. However, a relatively high frequency of early or late dislocation could reduce the potential benefits with THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…However, acetabular erosion is a complication of both unipolar and bipolar HA (occurring in up to 36% and up to 26% of hips, respectively) in the first five years postoperatively and often leading to revision surgery. 7,9 A recent Cochrane review showed an increased risk ratio of 3.83 for acetabular erosion in patients with unipolar HA. 3 In order to overcome both drawbacks and combine the advantages of THR (less pain, better function) and HA (shorter surgical time, less blood loss, greater stability), a large metal femoral head coupled with a pliable, 2.7 mm thick hydrophilic polycarbonate-urethane (PCU) acetabular component (TriboFit Hip System; Active Implants Corp., Memphis, Tennessee) was introduced for the treatment of displaced femoral neck fractures.…”
mentioning
confidence: 99%
“…However, acetabular erosion is a complication of both unipolar and bipolar HA (occurring in up to 36% and up to 26% of hips, respectively) in the first five years postoperatively and often leading to revision surgery. 7,9 A recent Cochrane review showed an increased risk ratio of 3.83 for acetabular erosion in patients with unipolar HA. 3 In order to overcome both drawbacks and combine the advantages of THR (less pain, better function) and HA (shorter surgical time, less blood loss, greater stability), a large metal femoral head coupled with a pliable, 2.7 mm thick hydrophilic polycarbonate-urethane (PCU) acetabular component (TriboFit Hip System; Active Implants Corp., Memphis, Tennessee) was introduced for the treatment of displaced femoral neck fractures.…”
mentioning
confidence: 99%
“…Dislocation is the major concern after both HA and THA for displaced femoral neck fractures in elderly patients. Previous studies have shown that the postoperative dislocation rate is higher in THA than in HA [ 28 , 29 ], whereas other studies have indicated no increase in the complication rate, including dislocation rate, after THA [ 6 , 7 ]. Our results showed that the risk of hip dislocation during the postoperative in-hospital period was significantly higher in the THA group than in the HA group dislocation (RD, 2.74%; 95%CI, 2.21–3.27; p < 0.001) which we supposed to be the main cause of the higher risk of revision surgery in the THA group (RD, 2.82; 95%CI, 2.27–3.37; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 In turn, clinical studies evaluating complications of arthroplasty for femoral neck fractures indicated higher primary and recurrent hip dislocation rates following THA as compared to HA. 28 , 29 This finding is likely due to the increased technical demands of THA, and any detrimental effects of procedural inexperience might be mitigated by high-volume arthroplasty hospitals.…”
Section: Discussionmentioning
confidence: 99%